THE RIGHTS OF MINORS IN CIVIL LAW - Abdusaminova Malika Timurovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores the rights of minors within the framework of civil law in Uzbekistan. With evolving socio-economic dynamics and increasing international integration, ensuring legal safeguards for minors has become a pressing concern in national legislation. The research analyzes both substantive and procedural rights, focusing on legal capacity, property rights, contract participation, and legal representation. By comparing Uzbekistan’s civil legislation with international norms, particularly the UN Convention on the Rights of the Child, the paper identifies gaps and opportunities for reform. The findings suggest that despite improvements, legal ambiguities and enforcement challenges persist, warranting deeper legislative and institutional refinement.